The Identification of Upwelling in the Occurrence of Tropical Cyclone Charlotte in the Waters of Southern Java (Case Study: March 17-28, 2022) - Muhammad Ridwan Prasetya; Avrionesti Avrionesti; Yosafat Donni Haryanto; Latifah Nurul Qomariyatuzzamzami (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2024)
Tropical cyclones are one of the meteorological phenomena that can have negative impacts on humans. These impacts can include heavy rainfall leading to floods and even storm surges. However, tropical cyclones can also have positive effects as they can trigger upwelling. Upwelling affects the fisheries aspect because in areas where upwelling occurs, sea surface temperatures are lower, and nutrients (such as phosphate and nitrate) are lifted from deeper layers of the ocean, which can affect the growth of phytoplankton. The objective of this research is to identify and analyze the upwelling phenomenon in the waters south of Java Island during the occurrence of Tropical Cyclone Charlotte. The data used in this research includes the intensity and movement direction of Tropical Cyclone Charlotte from the zoom.earth website and sea surface temperature, chlorophyll-a, mixed layer depth (MLD), and sea level anomaly data from the E.U. Copernicus Marine Service Information (CMEMS)-Global Monitoring and Forecasting Center during March 17-28, 2022. The results of this research indicate that upwelling was not identified during the period before or after the cyclone, as evidenced by sea surface temperatures between 28.5-29.5°C, chlorophyll-α concentration of <0.15 mg/m3, and a sea level rise of 0.1 m